2013
DOI: 10.5241/2f3-43
|View full text |Cite
|
Sign up to set email alerts
|

A practice report of students from a school for the blind leading groups of younger mainstream students in visiting a museum and making multi-modal artworks.

Abstract: Original citation:Hayhoe, Simon (2013) A practice report of students from a school for the blind leading groups of younger mainstream students in visiting a museum and making multi-modal artworks. Journal of blindness innovation and research, 3 (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It appears that there is willingness among exhibition-space personnel to learn and be trained to better assist individuals with disabilities, particularly to make them feel more comfortable during their visits. Museum staff's training has previously suggested as a way to deliver multisensory services to individuals with disabilities [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that there is willingness among exhibition-space personnel to learn and be trained to better assist individuals with disabilities, particularly to make them feel more comfortable during their visits. Museum staff's training has previously suggested as a way to deliver multisensory services to individuals with disabilities [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, conforming to [49,50], the employees of a museum should also be aware and informed of the principles of accessibility because they have the main responsibility to preserve it in those environments. In the research conducted by the authors of [25], it was found that people who worked in museums had not received any training on accessibility facilities and policies.…”
Section: Inclusive and Accessible Museumsmentioning
confidence: 99%
“…(Argyropoulos & Kanari, 2019;Golden & Walsh, 2013;Golding, 2012;Hooper-Greenhill, 2007;Melber & Brown, 2008;Pearson & Aloysious, 1994). Other researchers stress the importance of school visits in museums in relation to children's right for equal access to arts and culture and the enhancement of inclusive education and social inclusion (Aggelidis & Avraamidou, 2011;Hayhoe, 2013;Kanari, Argyropoulos & Filippatou, 2017;Spandagou, 2011). Thus, the collaboration between museums and schools as well as the development of various networks and forms of cooperation is very important (Argyropoulos & Kanari, 2019;Argyropoulos et al, 2017;Argyropoulos, Nikolaraizi, Chamonikolaou & Kanari, 2016;Hayhoe, 2013;Kanari, 2015;Kanari & Vemi, 2012;Pearson & Aloysious, 1994;Rosenberg, Schroder & Wheelock, 2003).…”
Section: Schools-museums Relationship and The Benefits For Children With Disabilitiesmentioning
confidence: 99%
“…T he motivation for the study was to develop collaborative learning using tablet technologies, along the same lines as previous tuition of mixed sighted and blind groups [1], support of blind students in higher education [2], and support of students with disabilities with similar technologies [3], [4].…”
Section: Introductionmentioning
confidence: 99%